DPP-based polymers with linear/branch side chain for organic field-effect transistors - Zhang, Daohai; Liang, Dongxu; Gu, Liang; Li, Jianhui; Zhang, Haichang (Frontiers in Chemistry, 2022)
For polymer semiconductors, the packing ability and molecular weight of polymers play a very critical role in their optoelectronic properties and carrier transport properties. In this work, two polymers, named Liner and Branch, are designed and synthesized with donor-acceptor (D-A) structure, based on diketopyrrolopyrrole (DPP) as electron acceptor and carbazole (CZ) as electron donor, and applied these two polymers in organic field effect transistors. Linear and branch have similar conjugated backbones, but different molecular weights and alkyl chains. The molecular weight and molecular aggregation ability on the carrier transfer efficiency are investigated. As a result, Linear exhibits better aggregation ability, but due to its smaller molecular weight than Branch molecule, the hole transfer efficiency of Linear (1.1×10-2 cm2 V -1 s-1 ) is slightly lower than that of Branch (2.3×10-2 cm2 V -1 s-1). This work proves that molecular weight is more important than molecular aggregation ability when designing organic field effect transistors for polymer semiconductors.